Web Based Information System Design in Elementary Schools - Chandra, Detri Amelia; Nofrianda, Erliyen; Febriansyah, Andri; Supriani, Anik (Journal of ICT Applications System, 2022)
This article aims to design and implement a Web-Based Information System in Elementary Schools. The method used in this research is to use the system development method with the Waterfall model. The type of data in this study is to use qualitative data. Web-Based Information System in Elementary School is designed using the UML (Unified Modeling Language) development method which consists of Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams. Database design using MySQL and system interface. The software used in the design and implementation of the system uses XAMPP as a web server, PHP and MySQL as a database. Web-Based Information System in elementary schools includes, login page, home page, profile page, student page, gallery, agenda page, student registration page, contact page, manage profile page, student manage page, gallery manage page, manage agenda page, page registration